2016
DOI: 10.1515/otmcj-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Strengths, weaknesses, opportunities and threats of virtual team in Nigerian construction industry

Abstract: The rationale behind any construction project varies; it might be to achieve value, time, quality, cost or just satisfaction for the client. Irrespective of any or all of these reasons, the team members involved in conception, inception, construction and delivery of a project are aware that a good teamwork is of essence. This is in the context of growing needs of client and the ever-growing improvement in methods of project delivery as influenced by technology. This article looks into the team type in the Nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…Finally, at a simplistic level, virtual teams are basically teams wherein the members operate from different geographical regions and function majorly with the aid of information and communications technology media. Odubiyi and Oke (2016) observed that Nigeria mainly uses the traditional team type (face-to-face team).…”
Section: Virtual Teams In Nigeriamentioning
confidence: 99%
“…Finally, at a simplistic level, virtual teams are basically teams wherein the members operate from different geographical regions and function majorly with the aid of information and communications technology media. Odubiyi and Oke (2016) observed that Nigeria mainly uses the traditional team type (face-to-face team).…”
Section: Virtual Teams In Nigeriamentioning
confidence: 99%
“…For instance, technology has effect on clients need and project delivery method (Odubiyi and Oke, 2016;Usman, 2012). Hence, construction professionals should be more flexible and open to new innovation by technology (Odubiyi and Oke, 2016). This is to meet up with the present age of globalization.…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria, as in other countries, primarily uses the traditional team type (face-to-face team) in construction works and that research about virtual teams is still in its nascent stages. Odubiyi and Oke (2016) found that communication among team members leading to flexibility of operation and decisionmaking was a key strength of virtual teams. The authors also found weaknesses among virtual teams.…”
Section: Nigerian Construction Industrymentioning
confidence: 99%